2012
DOI: 10.1093/toxsci/kfs067
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Elimination, and Biopersistence to 90 Days of a Systemically Introduced 30 nm Ceria-Engineered Nanomaterial in Rats

Abstract: Nanoceria is used as a catalyst in diesel fuel, as an abrasive in printed circuit manufacture, and is being pursued as an antioxidant therapeutic. Our objective is to extend previous findings showing that there were no reductions of cerium in organs of the mononuclear phagocyte (reticuloendothelial) system up to 30 days after a single nanoscale ceria administration. An ~5% aqueous dispersion of citrate-stabilized 30 nm ceria, synthesized and characterized in-house, or vehicle, was iv infused into rats terminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
128
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(140 citation statements)
references
References 62 publications
11
128
1
Order By: Relevance
“…Values listed under blots represent relative ratios of p-DRP1 S616 to total DRP1 protein normalized to actin nanoparticles to cross the BBB strikingly increased after injury (resulting in increased ROS/RNS). 57,58 By contrast, another study reported very small (2.9 nm diameter), citrate/ EDTA-stabilized CeO 2 nanoparticles administered intravenously to healthy rats appeared to cross the intact BBB, 56 suggesting that particle modifications might help improve neuronal delivery. In sum, considering the variability in findings to date, efficient delivery of nanoceria to neurons remains an important issue requiring further research and investigation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Values listed under blots represent relative ratios of p-DRP1 S616 to total DRP1 protein normalized to actin nanoparticles to cross the BBB strikingly increased after injury (resulting in increased ROS/RNS). 57,58 By contrast, another study reported very small (2.9 nm diameter), citrate/ EDTA-stabilized CeO 2 nanoparticles administered intravenously to healthy rats appeared to cross the intact BBB, 56 suggesting that particle modifications might help improve neuronal delivery. In sum, considering the variability in findings to date, efficient delivery of nanoceria to neurons remains an important issue requiring further research and investigation.…”
Section: Discussionmentioning
confidence: 98%
“…[56][57][58] In two of these studies, CeO 2 nanoparticles were administered intravenously and the concentration of nanoparticles was very low in the normal brain. 57,58 The study by Kim et al 57 used nanoceria that were surface modified with an artificial polymer phospholipid-polyethylene glycol, which is often added to nanoparticles to improve uptake and biodistribution, 59 yet these particles were also found only in low amounts in brain tissue. However, the ability of (a) Western blots of p-DRP1 S616, total DRP1 and actin protein levels from neurons exposed for 3 h to aged SNOC (100 mM), nanoceria (100 nM; 3 h pretreatment) or fresh SNOC (100 mM) alone or a combination of nanoceria (100 nM) and fresh SNOC (100 mM).…”
Section: Discussionmentioning
confidence: 99%
“…Advanced REACH Tool (ART) (Fransman et al, 2009) Occupational exposure assessment (Gorman et al, 2012) Occupational/consumer exposure assessment (Gottschalk et al, 2010a, 2010b, Sun et al, 2014, Gottschalk et al, 2009, Gottschalk et al, 2011 (Yokel et al, 2009, Yokel et al, 2012, Hardas et al, 2010, Dan et al, 2011 In vivoIkinetic tools for human exposure and hazard assessment (Lammel et al, 2013, Lammel andNavas, 2014) In vitro and in vivo tools for human hazard assessment…”
Section: Control Banding and Risk Screening Toolsmentioning
confidence: 99%
“…In order to fill this gap, several projects have developed and/or applied in vivo kinetic protocols. For instance, the U.S. STAR project developed methods to determine the distribution, persistence, translocation on and biotransformation of metal oxide MNs, their tolerability, and effects, focusing on oxidative stress endpoints (Yokel et al, 2009, Yokel et al, 2012, Hardas et al, 2010. This tool is an in vivo protocol including comprehensive physicochemical characterization for properties such as size, shape, zeta potential, extent of surface coating, and solubility.…”
Section: Behaviour and Fate Experimentsmentioning
confidence: 99%
See 1 more Smart Citation